Government Administration as the Main Prerequisite for Narrowing the corruption space - Сафончик, Оксана Іванівна; Сафончик, О. І.; Сафончик, Оксана Ивановна; Safonchyk, Oksana I.; Ріпенко, Артем Ігорович; Ріпенко, А. І.; Рипенко, Артем Игоревич; Ripenko, Artem I. (Baltija Publishing, 2019)
Political corruption as a social phenomenon exists in virtually all countries of the world, including those that most researchers consider as “benchmarks” in terms of the development of democracy. At the same time, there is a steady tendency towards the growth of political corruption and the evolution of corruption practices in developed democratic countries. Problems of political corruption in the professional literature are given a lot of attention but the issues related to the peculiarities of the experience of fighting political corruption in the EU in the context of the introduction of appropriate practices in Ukraine remain insufficiently researched. In the context of reforming the modern Ukrainian society, the study of problems of preventing and counteracting corruption is extremely relevant for a number of reasons: firstly, corrupt practices in the government machinery are the main obstacle to the implementation of any reforms; secondly, the high level of corruption in society, as evidenced by the results of the World CPI Corruption Perception Index 2015, decreases public confidence in the government; thirdly, it is necessary to implement the anti-corruption recommendations of the Action Plan on Visa Liberalization from the European Union (EU); fourthly, the reduction of corruption would contribute to attracting international investment, and so on. The purpose of the article is to identify features of counteraction to corruption in the countries of the European Union and to analyse the formation of government administration as the main precondition for narrowing the corruption space. To achieve this purpose, the following goals were set: to determine the level of implementation of international anti-corruption standards in the government practice of Ukraine; to investigate the formation and development of anti-corruption institutions; to analyse the experience of anti-corruption institutions in the EU; to investigate the formation of informational transparency of government space; to analyse the ratings of Ukraine regarding data openness; to find out the features of E-Declaration models as an element of public control of anti-corruption institutions in the system of public administration. Reaffirming its European aspirations, during 2001–2018, Ukraine ratified several laws in relation to the formation of anti-corruption standards: a) general and on liability for corruption offenses and offenses related to corruption; b) documents on the activities of specialized agencies for fighting corruption; c) documents on ethical rules, anti-corruption restrictions and prohibitions for certain officials and on the prevention of political corruption; d) documents on the prevention of corruption in the economy and sports; e) documents on access to information. This allows asserting that in general the legislative framework for the prevention of corruption in Ukraine has already been established. Despite the adoption of many laws, out of 200 anti-corruption measures, which, according to the State Program for the implementation of the Anticorruption Strategy, had to be implemented by state bodies by the end of 2018, about 35% had not been implemented. Anticorruption strategy for 2019 and subsequent years and the State Program for its implementation do not exist. Many important anti-corruption laws, which would help to further improve the Ukrainian economy, finance, the system of social protection of the population, and so on, were not adopted. Many of the problems that prevent effective use of the data obtained still need to be resolved. It is also necessary to find solutions for defining the electronic declaration of anti-corruption crusaders.

Політична корупція як соціальне явище існує практично в усіх країнах світу, у тому числі й у тих, які більшість дослідників вважають «еталонами» з точки зору розвитку демократії. Водночас у розвинених демократичних країнах спостерігається стійка тенденція до зростання політичної корупції та еволюції корупційних практик. Проблемам політичної корупції у фаховій літературі приділяється велика увага, але питання, пов'язані з особливостями досвіду боротьби з політичною корупцією в ЄС у контексті запровадження відповідних практик в Україні, залишаються недостатньо дослідженими. У контексті реформування сучасного українського суспільства дослідження проблем запобігання та протидії корупції є надзвичайно актуальним по ряду причин: по-перше, корупційні дії в державному апараті є основною перешкодою для здійснення будь-яких реформ; по-друге, високий рівень корупції в суспільстві, про що свідчать результати World CPI Corruption Perception Index 2015, знижує довіру населення до влади; по-третє, необхідно виконувати антикорупційні рекомендації Плану дій щодо лібералізації візового режиму Європейського Союзу (ЄС); по-четверте, зменшення корупції сприятиме залученню міжнародних інвестицій тощо. Метою статті є виявлення особливостей протидії корупції в країнах Європейського Союзу та аналіз формування державного управління як основної передумови звуження корупційного простору. Для досягнення цієї мети були поставлені такі цілі: визначити рівень впровадження міжнародних антикорупційних стандартів у державну практику України; дослідити становлення та розвиток антикорупційних інституцій; проаналізувати досвід антикорупційних інституцій ЄС; дослідити формування інформаційної прозорості державного простору; аналізувати рейтинги України щодо відкритості даних; з’ясувати особливості моделей електронного декларування як елемента громадського контролю антикорупційних інституцій у системі державного управління. Підтверджуючи свої європейські прагнення, Україна протягом 2001–2018 років ратифікувала декілька законів щодо формування антикорупційних стандартів: а) загальні та про відповідальність за корупційні правопорушення та правопорушення, пов’язані з корупцією; б) документи про діяльність спеціалізованих органів по боротьбі з корупцією; в) документи про етичні правила, антикорупційні обмеження та заборони для окремих посадових осіб та про запобігання політичній корупції; г) документи щодо запобігання корупції в економіці та спорті; д) документи про доступ до інформації. Це дозволяє стверджувати, що в цілому законодавча база щодо запобігання корупції в Україні вже створена. Незважаючи на ухвалення багатьох законів, із 200 антикорупційних заходів, які, згідно з Державною програмою реалізації Антикорупційної стратегії, державні органи мали виконати до кінця 2018 року, близько 35% не виконано. Не реалізовано Антикорупційну стратегію на 2019 та наступні роки та не існує Державної програми її реалізації. Не було прийнято багато важливих антикорупційних законів, які б сприяли подальшому вдосконаленню української економіки, фінансів, системи соціального захисту населення тощо. Багато проблем, які перешкоджають ефективному використанню отриманих даних, ще потребують вирішення. Також необхідно знайти рішення щодо визначення електронного декларування антикорупційних хрестоносців.
Safonchyk O. Government Administration as the Main Prerequisite for Narrowing the corruption space / O. Safonchyk, A. Ripenko // Baltic Journal of Economic Studies. - Vol. 5. – Iss. 3. - Baltija Publishing, 2019. - Р. 193-202.
Keywords: government administration; corruption; anti-corruption bodies; anti-corruption measures; ProZorro; E-Declaration; державне управління; корупція; антикорупційні органи; антикорупційні заходи; Е-декларація; Research Subject Categories::LAW/JURISPRUDENCE